"Ninguém quer uma pessoa trans por perto": escolas como espaços protetivos ou reprodutivos da transfobia - Sonetti, Sara Laham (2020)
This research seeks to analyze the effects that transphobia frequently reproduced in schools can have on the mental health of trans people. The school proves to be a very determinant space in the mental health and well-being of students, since it is a place where students spend a great deal of time. Discourse analysis based on 5 interviews, two of them with trans women and three with trans men, showed that the school can at times position itself as a protective space, with measures aimed at reducing injuries to the physical and mental health of trans people, becoming a welcoming and transforming environment in relation to the prevailing hegemonic pattern that is reproduced in intrafamily and social relationships. However, in the narratives, the reproduction by schools of transphobia predominated in their daily lives, showing the harmful effect of prejudice and discrimination, negatively influencing the mental health of trans people and making it difficult for them to stay in schools.